A study on the effectiveness of service delivery system towards customers satisfaction: A case study at road transportation department (RTD) of Melaka / Hazirah Ramli and Diana Uju - Ramli, Hazirah; Uju, Diana (Faculty of Administrative Science and Policy Studies, 2013)
The development of public administration not only contributes to the modernization of the public service but has also educated the public. Public expects the civil service to fulfil their needs in the best tune. Therefore, the quality of the services given by the public service, in all aspects, need to recognize the customers’ expectation. Realizing the important of improving the public service, this paper aimed to investigate the customer’s satisfaction towards service quality in the counter of the local authority. Even though the operation of each local authority followed the same operating procedures, but still the satisfaction rendered to the customers differ. With the intention of understanding and assisting the state government to improve their services, we decided to focus our study in the Road Transportation Department (RTD) of Melaka. The main objective of this study is to measure the effectiveness of services provided at the counter. The data were collected cross-sectionally. The scope concerning services delivery system at the counter and online services were selected to be the predictor of the dependent variable, which influences customer’s level of satisfaction.